713 Use of A Pre-Operative Investigation Checklist in Plastic Surgery Trauma. (4th May 2021) - Slade, R; Combellack, E; Kaur, A; Eales, M; O'Neill, T
Abstract: Introduction: In a regional centre for plastic surgery, it had been noted that operations were being delayed due to lack of pre-operative investigations. A pre-operative investigation checklist was developed between anaesthetic and surgical staff for semi-elective plastic trauma surgery patients, based on NICE guidelines. The checklist recommends which blood, radiology and cardiopulmonary tests would be appropriate based upon age, ASA grade and co-morbidity. Method: A complete cycle audit was used to evaluate the checklist. All patients having GA/block for plastic surgery trauma in a 2-week window were included. Data was collected retrospectively via electronic operative records, anaesthetic assessments, and clinical notes. A minimum of 15 patients was collected per cycle. A single page pre-operative checklist was created for pre-operative investigations were introduced after the first cycle. Results: The first audit cycle had 16 patients, ASA1 (5), ASA 2(6) ASA 3 (5). 75% had appropriate pre-op investigations. In the second cycle 22 patients, ASA 1 (8), ASA 2 (9), ASA 3 (3), ASA 4 (1). 100% of patients had appropriate pre-operative investigations. Conclusions: There was increased awareness of pre-operative investigations in medical and nursing staff after the introduction of the checklist. It has helped streamline the delivery of semi-elective trauma surgery in our unit.